2015
DOI: 10.1007/s13277-015-3340-3
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of miR-489 contributes into NSCLC cell invasion through targeting SUZ12

Abstract: microRNAs are small, non-coding RNAs that contribute into various biological processes during cancer progression. However, the potential role of miR-489 in the development of Non-Small Cell Lung Cancer (NSCLC) is not demonstrated. In present study, miR-489 was down-regulated both in tumor tissues and cells. Inhibition of miR-489 promoted cells invasion by using an invasion assay. Furthermore, miR-489 could regulate SUZ12 as shown by luciferase reporter and Western blot assays. Aberrant miR-489 expression could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 25 publications
3
19
0
Order By: Relevance
“…Moreover, miR-489 regulates ovarian cancer cell survival, growth and apoptosis via suppression of Akt3 [18]. miR-489 loss promotes invasion and epithelial-mesenchymal transition (EMT) events of lung cancer cells [30]. Recently, the expression miR-489 is found to be down-regulated in HCC tissues, especially in early recurrent cases, and miR-489 underexpression contributes to migration and invasion of HCC cells [20, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR-489 regulates ovarian cancer cell survival, growth and apoptosis via suppression of Akt3 [18]. miR-489 loss promotes invasion and epithelial-mesenchymal transition (EMT) events of lung cancer cells [30]. Recently, the expression miR-489 is found to be down-regulated in HCC tissues, especially in early recurrent cases, and miR-489 underexpression contributes to migration and invasion of HCC cells [20, 31].…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐489‐3p was originally reported that it might regulate early osteogenic differentiation in human mesenchymal stem cells, and has critical roles in osteogenesis . Although reduced expression levels of miR‐489‐3p is associated with several types of cancer metastasis , its role in OS metastasis has not been reported. In this study, we found that miR‐489‐3p expression was downregulated in OS cells and was also significantly decreased in metastatic lesions compared with their corresponding primary tumor samples, indicating miR‐489‐3p may be involved in OS metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that several proteins associated with tumor progression, such as protein tyrosine phosphatase PTPN11 , Akt3 , Smad3 and SUZ12 , had been identified as downstream effectors of miR‐489‐3p. It is not clear yet whether these proteins are also involved in invasion and metastasis of OS regulated by miR‐489‐3p.…”
Section: Discussionmentioning
confidence: 99%
“…One of these miRs, miR-133, has been shown to play a role in tumor suppression in a variety of cancers, including inhibiting breast cancer cell migration and invasion, gastric cancer cell growth and migration, and liver fibrosis (Esquela- Kerscher and Slack, 2006;Cheng et al, 2012;Liu et al, 2014;Mei et al, 2014;Wang et al, 2014;Yongchun et al, 2014;Xie et al, 2015;Zhang et al, 2015). Recent studies have shown that miRs may be a new regulatory mechanism involved in the onset of pituitary adenoma, providing a new method for the diagnosis and treatment of pituitary adenoma (Trivellin et al, 2012;Gadelha et al, 2013;Di Ieva et al, 2014;Leone et al, 2014).…”
Section: Introductionmentioning
confidence: 99%